Intensitas Menonton Tayangan Kekerasan, Tingkat Frustasi dan Agresi Pemain Futsal Di Liga Futsal Amatir - Rahardiankusuma, Dimas (Faculty of Psychology Universitas 17 Agustus 1945 Surabaya, 2016)
The purpose of this study is to determine the relationship between the intensity of watchingviolent footage and frustration level towards player’s aggression. The design of the study is using aquantitative approach. The population of the research is the futsal players in the league who playedin GOR Mangga Dua Surabaya. Samples were taken by accidental sampling technique for 77respondents. Data collection uses psychological scale of intensity of watching violence footagevariable, frustration variable and aggression variable scale using in a questionnaire. Collected databeing analyzed using IBM SPSS 20 for Macbook. Regression analysis results of this study indicatethe simultaneous relationship between intensity of watching violence footage and frustration againstaggression. The partial analysis shows that the intensity of watching violent footage has a positivecorrelation with aggression. The effective contribution of 17.2% showed a significant relationship.Other factors influencing aggression is temperature, poverty, provocation and anger. Based onthese results, researcher suggested for coaches who wishes their player’s aggression is controllableto have a different coaching method for the player to have emotion composure. Government shouldcome up with a new regulation for television broadcasting related to violent footageKeywords : aggression, intensity of watching violence footage, frustration